Moralitas Hukum dan Tindak Pidana Tanpa Korban: Kasus Prostitusi - Harahap, Maulana Alghifari; Batubara, Wahyudi; Harahap, Rindur Rodiah; Adelia, Nona; Lubis, Maysa Putri Khairana (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Prostitution is one of the controversial issues that raises debates between morality and legality. In the context of victimless crimes, prostitution is often seen as an act that does not directly harm others, but is still considered illegal in many countries, including Indonesia. This study aims to analyze how legal morality influences policies on prostitution as a victimless crime. With a normative legal approach and analysis of laws and regulations, this study found that law enforcement against prostitution is based more on moral considerations than on factual impacts on society. This study also highlights the need for legal reform that takes into account human rights and social realities. The problem of prostitution is indeed a classic problem that has long been a polemic, regarding this problem can give rise to pros and cons. If we look at it from the pros, it can be said that prostitution is an economic right carried out by a prostitution business actor, while if we look at it from the cons, prostitution is seen as a form of legalization of an illegal business that is contrary to an aspect of community morality, but on the other hand, a PSK herself can also be said to be a victim of the crime of prostitution made by the pimps, where the pimp has traded a human being where the human trafficking contains pornographic content carried out through the internet media.